Infrared thermography in equine practice - Čebulj-Kadunc, Nina (Array, 2020)
Thermography is a non-invasive diagnostic imaging method for the detection of mid to long-wave infrared radiation emitted from the body surface that allows visualization and quantification of changes in skin surface temperature. Within the electromagnetic spectrum, the wavelength of infrared radiation is too large to be detected by the human eye, although it is normally perceived as heat. Electromagnetic heat radiation can be registered with a thermal camera and visualized in the form of a temperature distribution map - a thermogram. The procedure is performed without physical contact with the examined object, including animals. Thermography can be used to determine physiological and pathological changes that induce variations of superficial temperature in a horse. These changes reflect blood flow patterns and the metabolic rate in the horse due to variations in heat production, such as exercise, injury, illness and environmental influence. Thermography has been used to evaluate several different clinical syndromes not only in the diagnosis of inflammation, but also to monitor the progression of healing. Thermography has important applications in research for the detection of illegal performance-enhancing procedures at athletic events and to determine the welfare of horses. Despite several advantages, it is also important to be aware of certain limitations surrounding the practical application of thermography. Therefore, the method should be used in combination with other diagnostic procedures rather than as a replacement.